DEFORESTATION POLICY GOVERNANCE IN INDONESIA - Yuza, Ahmad; Manaf, Halimah Abdul; Zainal, Zainal (CosmoGov: Jurnal Ilmu Pemerintahan, 2023)
Deforestation is a threat to national security and a disaster caused by natural and human factors. Natural factors, namely the dry season resulting in forest fires and the human factor which takes over the function of forests to become plantations and illegal logging. This paper uses a literature study with the theory of policy governance. The research method is a qualitative descriptive method. The results of the study show that accountability in the management and protection of forests in Indonesia has not run optimally due to overlapping policies and legal certainty relating to forests or land use in Indonesia is still ambiguous so that law enforcement is weakened and there is a lack of of quality resources in enforcement. Weak participation can also be seen from the policies implemented by the Indonesian government that have not been able to involve the involvement of local communities to avoid or reduce the rate of deforestation that occurs. While in terms of transparency carried out by the Indonesian government, one of which is through the SLVT policy to realize transparent government administration in forest management, which has shown results, although improvement efforts are still being made so that transparency criteria can be met to the fullest.gb777